Implementation of an Optical Character Recognizer (OCR) for Bengali language - Chowdhury, Muhammed Tawfiq; Islam, Md. Saiful; Bipul, Baijed Hossain (BRAC University, 2015)
Cataloged from PDF version of thesis report.